2004
DOI: 10.1063/1.1795654
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative multiphoton ionization of NO2 studied by time-resolved imaging

Abstract: We have studied dissociative multiphoton ionization of NO2 by time-resolved velocity map imaging in a two-color pump-probe experiment using the 400 and 266 nm harmonics of a regeneratively amplified titanium-sapphire laser. We observe that most of the ion signal appears as NO+ with approximately 0.28 eV peak kinetic energy. Approximately 600 fs period oscillations indicative of wave packet motion are also observed in the NO+ decay. We attribute the signal to two competitive mechanisms. The first involving thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
80
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(98 citation statements)
references
References 49 publications
14
80
3
1
Order By: Relevance
“…The NO + and photoelectron images basically consist of a central spot, indicating that the transient responsible of the oscillations is produced with almost no kinetic energy. These oscillations are similar to those previously recorded in experiments for which the pump and probe pulse were 400 nm and 266 nm, respectively [26,27]. In that case, oscillation periods of 600 fs and 830 fs and a much shorter damping time of about 3 ps were obtained from the time dependence of the zero kinetic energy photoelectrons and NO + transients.…”
Section: Resultssupporting
confidence: 87%
“…The NO + and photoelectron images basically consist of a central spot, indicating that the transient responsible of the oscillations is produced with almost no kinetic energy. These oscillations are similar to those previously recorded in experiments for which the pump and probe pulse were 400 nm and 266 nm, respectively [26,27]. In that case, oscillation periods of 600 fs and 830 fs and a much shorter damping time of about 3 ps were obtained from the time dependence of the zero kinetic energy photoelectrons and NO + transients.…”
Section: Resultssupporting
confidence: 87%
“…Only for the NO + fragment an enhancement is clearly observed at positive delay times, where the 400.4 nm photon is the pump and the 266.9 nm photon is the probe laser. In the pumpprobe experiments of Eppink et al 7 and Form et al, 8 an oscillatory NO + transient was observed at positive delay time. Such a oscillatory pattern is not very distinctly observed in our present data although the small increases in our NO + transients at 1000 and 1500 fs are reproducible.…”
Section: A Pump-probe Transientsmentioning
confidence: 90%
“…The effect of this conical intersection has been extensively studied in the frequency 5,6 and more recently also the time domain. [7][8][9][10] Depending on the typical time scale of the dissociation dynamics, femtosecond pump-probe laser spectroscopy can be used. However, the high field strength of femtosecond pulses easily induce multiphoton transitions in molecules and in general different competing photon pathways will contribute to the observed dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22] For C 2v geometries the two surfaces ͑ 2 A 1 and 2 B 2 ͒ intersect at a bond angle that depends on the bond length and form a one-dimensional CI seam. 17 The seam is located close to the bottom of the excited state and is readily accessible by a vibrational wavepacket launched onto the excited electronic surface from the Franck-Condon region of the ground state.…”
Section: Introductionmentioning
confidence: 99%